Development of cell‐penetrating peptide‐based drug leads to inhibit MDMX:p53 and MDM2:p53 interactions. Issue 6 (November 2016) - Philippe, Grégoire; Huang, Yen‐Hua; Cheneval, Olivier; Lawrence, Nicole; Zhang, Zhen; Fairlie, David P; Craik, David J.; de Araujo, Aline Dantas; Henriques, Sónia Troeira
Abstract : The transcription factor p53 has a tumor suppressor role in leading damaged cells to apoptosis. Its activity is regulated/inhibited in healthy cells by the proteins MDM2 and MDMX. Overexpression of MDM2 and/or MDMX in cancer cells inactivates p53, facilitating tumor development. A 12‐mer dual inhibitor peptide (pDI) was previously reported to be able to target and inhibit MDMX:p53 and MDM2:p53 interactions with nanomolar potency in vitro. With the aim of improving its cellular inhibitory activity, we produced a series of constrained pDI analogs featuring lactam staples that stabilize the bioactive helical conformation and fused them with a cell‐penetrating peptide to increase cytosol delivery. We compared pDI and its analogs on their inhibitory potency, toxicity, and ability to enter cancer cells. Overall, the results show that these analogs keep their nanomolar affinity for MDM2 and MDMX and are highly active against cancer cells. © 2016 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 106: 853–863, 2016.